PLAUSIBLE IMPACTS OF CLIMATE CHANGE ON POTATO IN SOME IMPORTANT POTATO GROWING POCKETS IN INDIA BASED ON INFERENCE FROM THEIR CLIMATE ANALOGUES - Govindakrishnan, P M; Singh, B P; Sharma, Samiksha; Rawat, Shashi (Potato Journal, 2015)
Â Â